Training on The Implementation of Practical Field Experience (PPL) Based On Lesson Study to Teachers of PPG FKIP Untad Partner Schools In East Palu-Mantikulore District, Palu City: Pelatihan Pelaksanaan Praktik Pengalaman Lapangan (PPL) Berbasis Lesson Study Kepada Guru-Guru Sekolah Mitra PPG FKIP Untad di Kecamatan Palu Timur-Mantikulore Kota Palu - Sabang, Sri Mulyani; Arwansyah, Arwansyah; Tahril, Tahril; Walanda, Daud Karel; Napitupulu, Mery (Mattawang: Jurnal Pengabdian Masyarakat, 2023)
Lesson Study is an approach to improving the quality of learning carried out by teachers collaboratively, with the main steps of designing learning to achieve goals, implementing learning, observing the implementation of the learning, and reflecting to discuss the learning studied and improve it and plan the next lesson. The main focus of implementing lesson study is student activities in class, with the assumption that student activities are related to teacher activities while teaching in class. In implementing PPL Education at UNTAD, the implementation of Lesson Study is integrated with the implementation of clinical supervision. The aim is to improve the quality of student learning outcomes and learning products. However, what is still experienced by the world of education today is that more than 50% of teachers do not understand and pay less attention to achieving and improving pedagogical and professional competence, including in schools in Palu City. To teach teachers to implement LS, it is not enough if teachers are introduced to what and how to implement it, but they also need to be introduced to why, what the long-term and short-term goals of implementation are. Teachers also need to be introduced to what the requirements are, what the difficulties and obstacles are in implementation, and that the main requirement for implementation is a commitment to benefit the nation's children. One of the critical characteristics of intelligent humans is that they not only know something but also how to respond and act on it.AbstrakLesson Study merupakan suatu pendekatan peningkatan kualitas pembelajaran yang dilaksanakan oleh guru secara kolaboratif, dengan langkah-langkah pokok merancang pembelajaran untuk mencapai tujuan, melaksanakan pembelajaran, mengamati pelaksanaan pembelajaran tersebut, serta melakukan refleksi untuk mendisukusikan pembelajaran yang dikaji tersebut dan menyempurkannya dan merencanakan pembelajaran berikutnya. Fokus utama pelaksanaan Lesson Study adalah aktivitas siswa di kelas, dengan asumsi bahwa aktivitas siswa tersebut terkait dengan aktivitas guru selama mengajar di kelas. Dalam penyelenggaraan PPL Kependidikan di UNTAD, penerapan Lesson Study diintegrasikan dengan penerapan supervisi klinis. Tujuannya untuk meningkatkan kualitas hasil belajar dan produk belajar siswa. Namun yang masih dialami oleh dunia pendidikan sampai saat ini adalah lebih besar 50% guru yang kurang memahami dan kurang memperhatikan pencapaian dan peningkatan kompetensi pedagogik dan professional, termasuk di sekolah-sekolah yang ada di Kota Palu. Untuk membelajarkan guru melaksanakan LS tidak cukup bila guru dikenalkan pada apa dan bagaimana melaksanakannya, tetapi juga perlu dikenalkan mengapa, apa tujuan jangka panjang dan jangka pendek pelaksanaan. Guru juga perlu dikenalkan pada apa persyaratannya, apa kesulitan dan hambatan pelaksanannya, dan bahwa persyaratan utama pelaksanannya adalah adanya komitmen untuk memaslahatkan anak bangsa. Salah satu ciri kritis manusia cerdas yakni tidak hanya mengetahui sesuatu tetapi juga bagaimana menanggapi dan menindaklanjutinya.